The living and the dead : a novel about a crime - Carlsson, Christoffer, 1986- (Hogarth, 2025)
"Two decades after an unsolved murder in a working-class town, another body turns up, ripping apart friendships and community--a captivating mystery and graceful investigation of brotherhood and family by a renowned criminologist."--